A Study Investigating The Relationship Between Tqm Practices And Sustainability In Banks (Journal of Namibian Studies : History Politics Culture, 2023)
Both public and private banks have recognized total quality management (TQM) as an important factor in their organizational success. In order to show how TQM practices, sustainability, and organizational performance are related, as well as how they affect organizational performance, this research is conducted. Its objective is to provide a conceptual model for further investigation into this connection. A questionnaire survey was administered to the banks in order to gather the data used in this research. This research delves into the complex web of connections between banking sustainability and Total Quality Management (TQM) strategies. Using a holistic approach, the study investigates how total quality management (TQM) principles—often linked to operational excellence—can aid in banks' pursuit of sustainability.